2016
DOI: 10.1186/s13024-016-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebrospinal fluid soluble TREM2 concentration in Alzheimer’s disease

Abstract: BackgroundThe discovery that heterozygous missense mutations in the gene encoding triggering receptor expressed on myeloid cells 2 (TREM2) are risk factors for Alzheimer’s disease (AD), with only the apolipoprotein E (APOE) ε4 gene allele conferring a higher risk, has led to increased interest in immune biology in the brain. TREM2 is expressed on microglia, the resident immune cells of the brain and has been linked to phagocytotic clearance of amyloid β (Aβ) plaques. Soluble TREM2 (sTREM2) has previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
247
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 258 publications
(278 citation statements)
references
References 38 publications
27
247
1
3
Order By: Relevance
“…Since PGRN is highly increased upon activation of microglia (Petkau et al , ), we speculate that increased CSF PGRN reflects elevated microglial function. It is well established that activation of microglia occurs in AD (Lyman et al , ; Heneka et al , ) and, in fact, we and others have previously shown that CSF sTREM2 also increases throughout the evolution of the disease (Heslegrave et al , ; Piccio et al , ; Suárez‐Calvet et al , ,b). A remarkable finding of this study is that higher CSF PGRN levels are associated with higher CSF sTREM2 levels exclusively when disease occurs (either in ADAD MC, late‐onset AD or in SNAP) but not in controls.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Since PGRN is highly increased upon activation of microglia (Petkau et al , ), we speculate that increased CSF PGRN reflects elevated microglial function. It is well established that activation of microglia occurs in AD (Lyman et al , ; Heneka et al , ) and, in fact, we and others have previously shown that CSF sTREM2 also increases throughout the evolution of the disease (Heslegrave et al , ; Piccio et al , ; Suárez‐Calvet et al , ,b). A remarkable finding of this study is that higher CSF PGRN levels are associated with higher CSF sTREM2 levels exclusively when disease occurs (either in ADAD MC, late‐onset AD or in SNAP) but not in controls.…”
Section: Discussionmentioning
confidence: 65%
“…The levels of CSF PGRN were significantly increased in MC compared to NC ( F 1,210 = 17.6, P = 0.00004, Fig A, ). In contrast to CSF sTREM2 (Henjum et al , ; Heslegrave et al , ; Piccio et al , ; Suárez‐Calvet et al , ,b), CSF PGRN was not significantly associated with age, neither in the entire sample (β = 0.118, P = 0.079), nor when stratifying by mutation status (for NC: β = 0.125, P = 0.283; for MC: β = 0.131, P = 0.142, Fig B). Consistent with previous publications (Nicholson et al , ; Morenas‐Rodríguez et al , ), CSF PGRN was higher in males than in females ( F 1,210 = 6.35, P = 0.012, Fig C) and were not affected by APOE ε4 status ( F 1,210 = 0.041, P = 0.840).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In AD patients, there are reports that sTREM2 levels correlate with those of total tau and phospho-tau in CSF, but not with Ab 1-42 levels [108][109][110]113]. Furthermore, studies of subjects with dominantly inherited AD have shown that CSF TREM2 elevation can occur approximately 5 years before onset of symptoms and after [ 5 6 5 _ T D $ D I F F ] an increase in Ab deposition and CSF tau levels [114].…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 97%
“…Whereas CSF sTREM2 is a topic of great interest as a potential marker for neurodegenerative diseases, the pathophysiological significance of serum blood sTREM2 remains unclear. Additionally, the function of sTREM2 has not been elucidated, although elevated sTREM2 levels in CSF have been suggested to reflect microglial activation in response to neuronal degeneration [27][28][29][30][31]. In this respect, recent studies uncovered sTREM2 as not just an inactive end-product but also a signaling molecule [15] that promotes macrophage survival by preventing apoptosis [32] and activates microglia to ultimately trigger inflammatory responses and prolong survival [33].…”
Section: Emerging Implications Of Trem2 and Strem2 In Neurodegeneratimentioning
confidence: 99%